2019
DOI: 10.1111/hepr.13363
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ribavirin therapy for chronic hepatitis E after kidney transplantation

Abstract: Hepatitis E virus (HEV) infection has been recognized as an acute condition. However, recent reports have shown that immunocompromised patients, such as those receiving solid‐organ transplantation, can develop chronic hepatitis with HEV infection. We report two cases of chronic hepatitis E after kidney transplantation (KT) who were successfully treated with ribavirin monotherapy. Several years after KT, both patients had sustained elevations in the levels of liver enzymes for a period of more than 6 months. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In this sense, clinical guidelines recommend a program therapy duration of 12 weeks using RBV at the initiation with a weight-adjusted dose or a dose adjusted on the basis of the estimated glomerular filtration rate [12,13,23]. Following these recommendations, a total of 176 transplant patients have been reported, and 129 of these patients have achieved SVR (73.2%) [11,[24][25][26][27][28][29][30][31][32][33]. Therefore, this recommendation seems to be highly effective for the treatment of HEV infection in transplant recipients infected by genotype 3 HEV.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, clinical guidelines recommend a program therapy duration of 12 weeks using RBV at the initiation with a weight-adjusted dose or a dose adjusted on the basis of the estimated glomerular filtration rate [12,13,23]. Following these recommendations, a total of 176 transplant patients have been reported, and 129 of these patients have achieved SVR (73.2%) [11,[24][25][26][27][28][29][30][31][32][33]. Therefore, this recommendation seems to be highly effective for the treatment of HEV infection in transplant recipients infected by genotype 3 HEV.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with previous observations, showing more than 80% of viral clearance after 3 months of antiviral treatment with ribavirin. 2,8,9 Previous studies already identified risk factors for treatment failure of chronic HEV infection. Immunosuppressive therapy with tacrolimus instead of cyclosporine A 6 and a low lymphocyte count at therapy initiation 7 have been shown to be associated with a decreased response to therapy.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…6 In the absence of spontaneous clearance, the treatment option of choice is ribavirin, 7 resulting in HEV clearance after 3 months in up to 78%-100% of patients. 4,7,8 However, ribavirin therapy carries the risk of adverse effects, such as anemia due to bone marrow toxicity. 7,9 The appropriate treatment of HEV infection in immunosuppressed patients remains controversial, mostly due to the lack of controlled trials and overall small numbers of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial management for chronic infection is to reduce immunosuppressive therapy leading to the elimination of HEV in approximately 30% of patients . Alternatively, treatment with ribavirin (RBV) is effective . Recently, several mutations of HEV were detected in RBV treatment failure patients .…”
Section: Introductionmentioning
confidence: 99%